Performance Analysis on Different Rotor Topologies of Interior Permanent Magnet Synchronous Motor - Aziz, Roziah; Che Yassin, Fakhrul Rusyaidi (Evolution in Electrical and Electronic Engineering, 2020)
A performance comparison between three different types of interior permanent magnet synchronous motor rotor topologies, namely InSet, Nissan LEAF, and Multiple-Barrier in the 2-dimensional model. This analysis was conducted to see which model design is the best among the three different IPMSM models of rotor topologies and the parameters observed parameters such as cogging torque, back electromotive force, three-phase test, zero rotor position test, flux line, and load parameters result such as torque versus armature coil current density and torque and power versus speed. This analysis was conducted by using JMAG Designer 16.1 software. The Geometry Editor will be used for sketching the models then import to JMAG Designer to perform the simulation by inserting the correct parameters such as materials, conditions, circuit, meshing and properties. Both studies are successfully simulated and manage to obtain the result. For the first study, which is for the 2-dimensional model, the analysis performed is a simulation test without load and also has loaded. After the simulation test is completed, the results obtained are being compared and analyzed to determine which design is the best and based on the analysis found that InSet design is the best design compared with the other two designs.